TERRITORIAL ANALYSIS OF COMPONENTS OF STRUCTURAL ELEMENTS OF THE UKRAINIAN BLACK SEA REGION ECOLOGICAL NETWORK - YavorskаViktoria (Human Geography Journal, 2015)
In provided article the distribution on the territory of the Ukrainian Black Sea region one of the most important elements of the ecological network – objects of Nature Conservation Fund was analyzed. The problems arising from the formation of the ecological network associated with excessive development of the territory were reviewed. It was described the main components of the structural elements of the regional ecological network. Schematic map with different marked areas of territories that may be included in the regional ecological network was developed. The ways of increasing the area of ecological network in the region was proposed.